Technique Comparative Analysis of OTT TV and IPTV - Weijia Shi; Li Jiang; Liding Jia (Dianxin kexue)
With the development of OTT TV service, more and more influences on IPTV service were brought. So based on the current situation, the different technical realizations between OTT TV and IPTV were discussed. And the theory of video coding technique, steaming transmission technique and terminal technique were expound, specially the differences between OTT TV and IPTV were compared. Then the reasons of making these differences were found, accordingly the direction and trend of IP video service technique were predicted.